2017
DOI: 10.1007/s00408-017-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Dimensions as a Prognosticator of Transplant-Free Survival in Scleroderma Interstitial Lung Disease

Abstract: In SSc-ILD patients, a PA:Ao ratio ≥1.1 is associated with higher risk of lung transplant or death. These data suggest that PA:Ao dimension may be used for prognostication in SSc-ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Analyses adjusting for the presence or absence of radiographic honeycombing demonstrated that the presence of MLN enlargement predicts TFS (HR, 1.45; 95% CI, 1.06-1.99; P = 0.022) and respiratory hospitalization (internal rate of return [IRR], 1.62; 95% CI, 1.09-2.41; P = 0.017) independent of radiographic honeycombing. Additional sensitivity analyses adjusting for PA diameter measurements as a surrogate for pulmonary hypertension (28)(29)(30) demonstrated that presence of MLN enlargement predicts TFS and respiratory hospitalization independent of PA diameter (HR, 1.53; 95% CI, 1.11-2.10, P = 0.009 and IRR, 1.57, 95% CI, 1.05-2.34, P = 0.028, respectively) or PA/aorta ratio (HR, 1.51; 95% CI, 1.10-2.08; P = 0.012 and IRR, 1.69; 95% CI, 1.14-2.51; P = 0.009, respectively).…”
Section: Primary Outcome Assessmentmentioning
confidence: 99%
“…Analyses adjusting for the presence or absence of radiographic honeycombing demonstrated that the presence of MLN enlargement predicts TFS (HR, 1.45; 95% CI, 1.06-1.99; P = 0.022) and respiratory hospitalization (internal rate of return [IRR], 1.62; 95% CI, 1.09-2.41; P = 0.017) independent of radiographic honeycombing. Additional sensitivity analyses adjusting for PA diameter measurements as a surrogate for pulmonary hypertension (28)(29)(30) demonstrated that presence of MLN enlargement predicts TFS and respiratory hospitalization independent of PA diameter (HR, 1.53; 95% CI, 1.11-2.10, P = 0.009 and IRR, 1.57, 95% CI, 1.05-2.34, P = 0.028, respectively) or PA/aorta ratio (HR, 1.51; 95% CI, 1.10-2.08; P = 0.012 and IRR, 1.69; 95% CI, 1.14-2.51; P = 0.009, respectively).…”
Section: Primary Outcome Assessmentmentioning
confidence: 99%
“…The ratio was able to detect patients with PH [2][3][4][5][6], it correlated with hemodynamics [7][8][9][10], and it was predictive for morbidity [11][12][13] and mortality [14][15][16][17]. Different cutoffs for PA:A have been suggested to identify PH, depending on the methodology (CMR or CT), ranging from 0.83 to >1 [2,14,[18][19][20][21]. Previously, no TTE cutoffs have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 2 studies found increased rates of transplantation and death in patients with interstitial lung disease and higher PA:AA. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%